Membangun Kesiapan Belajar Membaca di Jenjang Prasekolah - Adelani, Risa (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
Currently, the practice of learning to read formally is mostly done at the preschool level. Many experts oppose this, but there are also those who support it. In this paper, we will discuss how educational programs at the preschool level should prepare children to learn to read formally. The discussion includes the stages of reading ability, the concept of reading readiness, and the age of reading readiness.